Molecular Docking of Xanthone Derivatives as Therapeutic Agent for Covid-19 - Emmy Yuanita; Sudirman Sudirman; Ni Komang Tri Dharmayani; Maria Ulfa; Saprizal Hadisaputra; Jufrizal Syahri (Molekul, 2022)
Covid-19 has caused more than 14 million confirmed cases and more than 6 hundred deaths as of 21 July 2020 globally. However, there is no approved drug to treat the disease. Xanthone is a potential therapeutic option for the virus that have been tested using molecular docking. There were 12 of xanthone compounds and its derivatives which have been docked against two protein crystals, 2GX4.pdb and 6FV1.pdb, which obtained two potential compounds of hydroxyxanthone derivatives with sulfonate and chloro substitution. These compounds are potentially developed into one of the agents for the treatment of infection COVID-19 disease. Based on energy data and interactions with amino acid residues when compared with its own native ligands, namely NOL and E8E, respectively. Energy docking and energy docking interactions are equal to - 43.3057and - 45.5805 Kcal/mol respectively, during interactions with amino acid residues in the form of Gly 142, His 163, Cys144, Glu166, Gln164 and His 41. Based on these two data, it can be concluded that trihydroxyxanthone compounds 4 and 8 with chloro and sulfonate substitution are very potential to be developed as drug agents for Covid-19 disease therapy through protease inhibition.